meningkatkan proses pembelajaran di sekolah menengah atas, dengan memanfaatkan "Sapiens: Sebuah Sejarah Singkat Umat Manusia" sebagai sumber belajar yang efektif - Handziko, Rio Christy; Widiatmika, Dippya Kharisma (Biosfer: Jurnal Pendidikan Biologi, 2024)
Understanding human evolution can be challenging for students and may lead to misconceptions, often stemming from the learning materials employed. Current learning resources commonly include textbooks, images, and the internet. The popular science book "Sapiens: A Brief History of Humankind" offers potential as an educational tool for teaching human evolution. This study aims to assess the suitability of "Sapiens" for high school Biology education and its potential as a resource for teaching human evolution in senior high school. Employing a qualitative descriptive method with a content analysis approach, data is gathered through documentation techniques. Primary data is derived from the documentation and content analysis of "Sapiens: A Brief History of Humankind." Data analysis follows the model proposed by Miles and Huberman (1983), encompassing data reduction, presentation, and conclusion drawing. The findings indicate that the book effectively addresses 7 out of 9 (77.78%) sub-topics of human evolution commonly taught in high school Biology. Importantly, the book replaces outdated terms like Pithecantropus and Megantropus paleojavanicus, found in traditional textbooks. Moreover, the book fulfills the five criteria for selecting learning resources as outlined by Djohar (1987). Consequently, "Sapiens" can serve as a valuable learning resource for high school Biology, particularly regarding the study of human evolution.